Odpowiedź :
a)4(x-5y)+3(x+8y)=4x-20y+3x+24y=7x+4y
b) 5(a-2b-1)-3(a-4b)=5a-10b-5-3a+12b=2a+2b-5
b) 5(a-2b-1)-3(a-4b)=5a-10b-5-3a+12b=2a+2b-5
a) 4x-20y + 3x+24y = 7x+4y
b)5a-10b-5-3a+12b=2a+2b-5
c)5a-4a+12b-4+8+a-9b=2a+3b+4
d)-2a+6b-6-14b+21a+14-20a+15b=-a+23b+8
b)5a-10b-5-3a+12b=2a+2b-5
c)5a-4a+12b-4+8+a-9b=2a+3b+4
d)-2a+6b-6-14b+21a+14-20a+15b=-a+23b+8
a)4(x-5y)+3(x+8y)=4x- 20y+ 3x+24y=7x+4y
b) 5(a-2b-1)-3(a-4b)=5a-10b-5-3a+12b=2a+2b -5
c) 5a-4(a-3b+1)+8+(a-9b)=2a-4a+12b+12+8+a-9b=-a+3b+20
d) -(2a-6b+6)-7(2b-3a+2)-5(4a-3b)=2a+6b-6-14b+21a-14-20a+15b= 3a+23b-20
b) 5(a-2b-1)-3(a-4b)=5a-10b-5-3a+12b=2a+2b -5
c) 5a-4(a-3b+1)+8+(a-9b)=2a-4a+12b+12+8+a-9b=-a+3b+20
d) -(2a-6b+6)-7(2b-3a+2)-5(4a-3b)=2a+6b-6-14b+21a-14-20a+15b= 3a+23b-20